Migration from hierarchal storage management to ASM storage server: a case study...Proccedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston TX, May 6-9, 1999 - Baune D; Bookman G (Journal of Digital Imaging)
The Department of Radiology at the University of Utah Hospitals and Clinics had to make a change from its current hierarchical storage management (HSM) system. The HSM software is the heart of any near-line data storage system and any change in this software affects all near-line and on-line data storage. In this case, over a terabyte of data had been migrated in more than 2 million files. The traditional method of reading in the old data and then writing it out to the new system was calculated to take more than 60 years. Here, we will examine the reasons for making such a radical change in the HSM used. We will also discuss why ASM (the new HSM software) was selected, and the performance improvements seen. A second, less difficult transition was made a few months later, of upgrading to a newer faster tape technology. The two types of tapes were incompatible, but the storage software and robotics used allowed for a peaceful coexistence during the transition. The transition from HSM to ASM was not a trivial task. It required a reasonable implementation/migration plan, which involved finding the correct resources and thinking outside the norm for solutions. All sites that have any amount of data stored in near-line devices will face similar conversions. This presentation should help in the event that a data conversion plan is not already in place. Copyright (c) 1999 by W.B. Saunders Company